2010
DOI: 10.1186/1749-8090-5-73
|View full text |Cite
|
Sign up to set email alerts
|

An alternative surgical approach to subclavian and innominate stenosis: a case series

Abstract: We report three cases of symptomatic stenosis of the great vessels or supra-aortic trunks successfully treated surgically with aorto-subclavian and aorto-innominate bypass. Two were performed via manubriotomy and a third case via standard median sternotomy because of concomitant coronary revascularisation. There was complete symptomatic relief on follow-up, and radiological imaging confirmed good flow in the grafts and post-stenotic arteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Second, the aorto-supra aortic trunk bypass reportedly provides a more physiological blood flow pattern than cerebral approaches, such as a carotid-subclavian bypass. 6 Furthermore, in our patient, the ascending aorta and distal site of the left CCA were seen to be relatively healthy. Therefore, the side-bite clamping of the ascending aorta and clamping of the distal left CCA were considered to be a safe procedure.…”
Section: Discussionmentioning
confidence: 49%
“…Second, the aorto-supra aortic trunk bypass reportedly provides a more physiological blood flow pattern than cerebral approaches, such as a carotid-subclavian bypass. 6 Furthermore, in our patient, the ascending aorta and distal site of the left CCA were seen to be relatively healthy. Therefore, the side-bite clamping of the ascending aorta and clamping of the distal left CCA were considered to be a safe procedure.…”
Section: Discussionmentioning
confidence: 49%
“…Berguer et al [ 2 ] reported that, in comparison to the cervical approach, the transthoracic approach has a relatively higher morbidity but more durable results in atherosclerotic disease involving complex and multiple supra-aortic trunk vessels. Khalil et al [ 5 ] reported successful open surgery with a transthoracic approach in three patients using an aorto-subclavian or aorto-innominate artery bypass. Aorto-supra aortic trunk bypass is reportedly safe in patients with concomitant carotid disease with reduced cerebral risks, avoids endarterectomy and its attendant thrombotic risks, and provides a more physiological blood flow pattern than axillo-axillary or carotid-subclavian bypass [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Khalil et al [ 5 ] reported successful open surgery with a transthoracic approach in three patients using an aorto-subclavian or aorto-innominate artery bypass. Aorto-supra aortic trunk bypass is reportedly safe in patients with concomitant carotid disease with reduced cerebral risks, avoids endarterectomy and its attendant thrombotic risks, and provides a more physiological blood flow pattern than axillo-axillary or carotid-subclavian bypass [ 5 ]. In our patient, a direct ultrasonographic examination revealed severe atheromatous plaques inside the brachiocephalic trunk, and so we chose the right subclavian artery as the distal anastomosis site for the prosthetic bypass conduit.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that they excluded patients from their study with long stenoses (>4 cm) and those with complete occlusion of the subclavian artery, which can easily be corrected surgically. [19] The use of PTA for occlusive disease of the subclavian artery is increasing, but open surgical reconstruction remains an effective treatment option with good long-term results. [20,21] Kretschmer et al [9] found a statistically significant greater patency rate with transposition over bypass, and the universal experience in the small series of reported transpositions in the literature indicates that patency is almost always 100%.…”
Section: Discussionmentioning
confidence: 99%